2020
DOI: 10.1177/0025817220965377
|View full text |Cite
|
Sign up to set email alerts
|

Mental health of forensic odontologists in Covid-19: An Indian perspective

Abstract: Forensic autopsies provided guidance and clarification on the transmission of and the safety of working with Covid-19. However, the outbreak induced not just a socio-economic crisis, but a fast-paced psychological distress worldwide. Various psychological and mental health problems, including stress, anxiety, depression, frustration and uncertainty, have gradually emerged. This article brings attention to the mental health of forensic odontologists during the pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…The research of Johnson et al [19] , based on forms sent to Indian forensic odontologists, found that it is necessary to implement protocols for the virus infection prevention but also to provide the healthcare workers with the necessary safety conditions to cope with emergencies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research of Johnson et al [19] , based on forms sent to Indian forensic odontologists, found that it is necessary to implement protocols for the virus infection prevention but also to provide the healthcare workers with the necessary safety conditions to cope with emergencies.…”
Section: Discussionmentioning
confidence: 99%
“…Many more difficulties, which may explain the trend, affected this phase: quarantines, travelling restrictions, limits of access to Courts and public offices, evaluation " per tabulas" or tele-medicine visits. Among the difficulties reported, there were also problems in the triage procedures, reduction, re-programming or postponement of the visits, problems in the use of the PPE (especially the FFP2/KN95 masks) [19] , [20] , [21] and in keeping the social distancing rules properly which in some cases caused complains to the FOd appointed by the Court.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, proper handling of the tissues and equipment is required during transportation and storage. 2,7…”
Section: Forensic Odontologist and Covid-19mentioning
confidence: 99%
“…Adequate knowledge and training regarding 'Donning and Doffing' may reduce the source of contamination. 2 Personal protective equipment includes a disposable head wear, long-sleeved water resistant gown, double pair of disposable gloves, N95 respirator or FFP2/ FFP3 face mask, disposable face shield, goggles and shoe cover. 7 Changing of apron, gown or PPE between contacts is essential and proper hand washing measures to be taken after removing the PPE to prevent any surface contamination.…”
Section: Guidelines/recommendations During Identification Processmentioning
confidence: 99%
See 1 more Smart Citation